Direct driven axial flux permanent magnet generator for small-scale wind power applications - Ferreira, Ângela P. (2014)
The use of direct driven generators in small-scale wind power conversion systems, instead of geared machines, reduces the number of drive components, which offers the opportunity to reduce costs and increases system reliability and efficiency. For such applications, characterized by low speed of rotation, the axial flux permanent magnet generator is particularly suited, since it can be designed with a large pole number and high torque density.